Proceedings of the 42nd International Academic Conference, Rome 2018
DOI: 10.20472/iac.2018.042.024
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Ostracism as a Predictor of Employee Performance and Employee Turnover- Evidence From the Banking Sector

Abstract: Workplace ostracism has been identified as a separate entity from workplace harassment. Practised through banishing the target from a social group and social interaction, workplace ostracism is probable to have negative impact on the employees. Though different from harassment, it is equally destructive when it comes to the workplace environment. It manifests itself in a number of forms not only at individual level but also at the organizational level. This paper aims to explore the effects of ostracism on emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
(32 reference statements)
1
1
0
Order By: Relevance
“…Thus, this study showed that workplace expulsion significantly negatively impacts work engagement in Pakistan's banking sector. It has also been demonstrated that workplace ostracism significantly negatively impacts psychological empowerment in Pakistan's banking sector; the findings of a similar study conducted by (Javed et al, 2018) parallel the results. This study confirms that psychological empowerment significantly and positively affects staff's work engagement in the Pakistani banking sector, and the results are similar to those conducted by Meng & Sun (2019).…”
Section: Discussionsupporting
confidence: 54%
“…Thus, this study showed that workplace expulsion significantly negatively impacts work engagement in Pakistan's banking sector. It has also been demonstrated that workplace ostracism significantly negatively impacts psychological empowerment in Pakistan's banking sector; the findings of a similar study conducted by (Javed et al, 2018) parallel the results. This study confirms that psychological empowerment significantly and positively affects staff's work engagement in the Pakistani banking sector, and the results are similar to those conducted by Meng & Sun (2019).…”
Section: Discussionsupporting
confidence: 54%
“…Reducing ostracism can decrease employee absenteeism and delays, and improve employees' creativity and innovation (8). This has led to the perception of the need to reduce ostracism in today's organizations as an important issue (9). Ostracism is a psychological phenomenon that not only has primary effects at the individual level and involves the psychologically disadvantaged individual but also has consequences at the group and organizational levels (10,11).…”
Section: Introductionmentioning
confidence: 99%